A gut response - Nicotra, Matthew L (eLife, 2017)
Unexpected findings from the immune system of sea urchin larvae potentially provide insights into immune signaling in ancestral animals.
Keywords: Strongylocentrotus purpuratus; gut immunity; echinoderm; cytokines